Analyzing the therapeutic efficacy of bis-choline-tetrathiomolybdate in the Atp7b−/− copper overload mouse model - Kim, Philipp; Zhang-Hagenlocher, Christine; Thoröe-Boveleth, Sven; Buhl, Eva Miriam; Weiskirchen, Sabine; Stremmel, Wolfgang; Merle, Uta; Weiskirchen, Ralf (Biomedicines, 2021)
Bis-choline-tetrathiomolybdate, introduced as WTX101 (now known as ALXN1840), is a first-in-class copper-protein-binding agent for oral therapy of Wilson’s disease. In contrast to other decoppering agents such as trientine or D-penicillamine it acts by forming a tripartite complex with copper and albumin, thereby detoxifying excess liver and blood copper through biliary excretion. Preclinical animal experimentation with this drug was typically done with the alternative ammonium salt of tetrathiomolybdate, which is expected to have identical properties in terms of copper binding. Here, we comparatively analyzed the therapeutic efficacy of ALXN1840, D-penicillamine and trientine in lowering hepatic copper content in Atp7b−/− mouse. Liver specimens were subjected to laser ablation inductively conductively plasma mass spectrometry and electron microscopic analysis. We found that ALXN1840 caused a massive increase of hepatic copper and molybdenum during early stages of therapy. Prolonged treatment with ALXN1840 reduced hepatic copper to an extent that was similar to that observed after administration of D-penicillamine and trientine. Electron microscopic analysis showed a significant increase of lysosomal electron-dense particles in the liver confirming the proposed excretory pathway of ALXN1840. Ultrastructural analysis of mice treated with dosages comparable to the bis-choline-tetrathiomolybdate dosage used in an ongoing phase III trial in Wilson’s disease patients, as well as D-penicillamine and trientine, did not show relevant mitochondrial damage. In contrast, a high dose of ALXN1840 applied for four weeks triggered dramatic structural changes in mitochondria, which were notably characterized by the formation of holes with variable sizes. Although these experimental results may not be applicable to patients with Wilson’s disease, the data suggests that ALXN1840 should be administered at low concentrations to prevent mitochondrial dysfunction and overload of hepatic excretory pathways.